Konsep Relasi Ayah dan Anak Dalam Perspektif Tafsir Al Azhar Sebagai Respon Fenomena Fatherless di Indonesia - Masturoh, Siti Apriliana (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2024)
This study explores the concept of father-child relationships in the Tafsir Al-Azhar as a response to the increasing phenomenon of fatherlessness in Indonesia, using psychological analysis based on Albert Bandura’s social learning theory. Employing a qualitative descriptive-analytical method, this study analyzes Tafsir Al-Azhar by Buya Hamka. The findings show that the father plays a crucial role as a moral role model, spiritual educator, and guide in matters of faith, communication, trust, affection, and respect, particularly in the context of giving advice. Additionally, patience and wisdom in facing challenges, dedication and love in parenting, personal influence and individual responsibility, differences in belief within the family, as well as the role of the father as a protector of his children, are emphasized. Bandura’s theory supports the notion that a positive father figure contributes to shaping children’s behavior through observation and imitation. This study concludes that understanding the father-child relationship in the context of the Tafsir Al-Azhar can help address the fatherlessness phenomenon and foster a generation of virtuous individuals.